2013
DOI: 10.1002/btpr.1739
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of mammalian cell culture performance through surfactant enabled concentrated feed media

Abstract: The design of basal and feed media in mammalian cell culture is paramount towards ensuring acceptable upstream process performance in various operation modes, especially fed-batch culture. Mammalian cell culture media designs have evolved from the classical formulations designed by Eagle and Ham, to today's formulations designed from continuous improvement and statistical frameworks. Feed media is especially important for ensuring robust cell growth, productivity, and ensuring the product quality of recombinan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Stability issues with cell culture media have been previously associated with HTST treatment (Floris et al, 2018) or with extended storage in the cold or at room temperature (Hossler, McDermott, Racicot, & Fann, 2013;Kuschelewski, Schnellbaecher, Pering, Wehsling, & Zimmer, 2017;McCoy, Costa, & Morris, 2015). These extensive investigations identified a number of root causes for media F I G U R E 3 (a) Effect of pCO 2 model, media hold, and Mn supplementation on afucosylation of mAb at time of harvest (Day 12) in a full-factorial DOE study.…”
Section: Effects Of Pco 2 Level Media Hold Duration Media Htst Trmentioning
confidence: 99%
“…Stability issues with cell culture media have been previously associated with HTST treatment (Floris et al, 2018) or with extended storage in the cold or at room temperature (Hossler, McDermott, Racicot, & Fann, 2013;Kuschelewski, Schnellbaecher, Pering, Wehsling, & Zimmer, 2017;McCoy, Costa, & Morris, 2015). These extensive investigations identified a number of root causes for media F I G U R E 3 (a) Effect of pCO 2 model, media hold, and Mn supplementation on afucosylation of mAb at time of harvest (Day 12) in a full-factorial DOE study.…”
Section: Effects Of Pco 2 Level Media Hold Duration Media Htst Trmentioning
confidence: 99%
“…Specifically, the addition of 0.01% (v/v) Polysorbate 80 into chemically defined concentrated feed media reduced overall aggregation levels by 2.6-2.7% of two different CHO cell lines. However, in this study, it was rather the enriched feed media including Polysorbate 80 than the surfactant itself, which was responsible for the decrease in aggregation, since the medium osmolality significantly increased as a consequence of more concentrated medium 176 . A current work described the inhibitory capacities of trehalose, an approved additive used in drug substance and drug product formulation.…”
Section: Aggregatesmentioning
confidence: 76%
“…Iron plays a major role in inhibiting the formation of aggregate forms, as shown in long-term drug substance stability studies, where the abundance of high-molecularweight species was significantly lower at low iron concentrations (0-4 ppm) in the presence of a chelator 174 . Surfactant containing culture media were reported to stabilize the expressed protein and thus reduce aggregation 175,176 . Specifically, the addition of 0.01% (v/v) Polysorbate 80 into chemically defined concentrated feed media reduced overall aggregation levels by 2.6-2.7% of two different CHO cell lines.…”
Section: Aggregatesmentioning
confidence: 99%
“…The only combination of insulin and transferrin had also proven to increase 18% TNFR‐Fc production in a GS‐CHO cell line and prourokinase production in 11G‐S CHO cells . Tween 80 has recently been demonstrated to have a beneficial effect on mAb production in CHO‐K1 and CHO DUX‐B11 . The authors mention that the interest in using tween 80 relies on its capacity to extend the stability of media compounds in solution for a longer period of time, which spans their availability in the culture medium.…”
Section: Discussionmentioning
confidence: 99%
“…Tween 80 is a nonionic surfactant and emulsifier frequently used to prevent cell clumping . Interestingly, it has also been recently reported that it improves protein production in different mammalian cell types . Selenium is an essential trace element for normal cell growth and development.…”
Section: Introductionmentioning
confidence: 99%